Self-interaction corrected LDA + U investigations of BiFeO3 properties: plane-wave pseudopotential method. (3rd November 2015) - Yaakob, M K; Taib, M F M; Lu, L; Hassan, O H; Yahya, M Z A
Abstract: The structural, electronic, elastic, and optical properties of BiFeO3 were investigated using the first-principles calculation based on the local density approximation plus U (LDA + U) method in the frame of plane-wave pseudopotential density functional theory. The application of self-interaction corrected LDA + U method improved the accuracy of the calculated properties. Results of structural, electronic, elastic, and optical properties of BiFeO3, calculated using the LDA + U method were in good agreement with other calculation and experimental data; the optimized choice of on-site Coulomb repulsion U was 3 eV for the treatment of strong electronic localized Fe 3d electrons. Based on the calculated band structure and density of states, the on-site Coulomb repulsion U had a significant effect on the hybridized O 2p and Fe 3d states at the valence and the conduction band. Moreover, the elastic stiffness tensor, the longitudinal and shear wave velocities, bulk modulus, Poisson's ratio, and the Debye temperature were calculated for U  = 0, 3, and 6 eV. The elastic stiffness tensor, bulk modulus, sound velocities, and Debye temperature of BiFeO3 consistently decreased with the increase of the U value.